Comparison of Bracket Failure with Resin Modified Glass Ionomer Cement and Resin-Based Adhesive: Resin Modified Glass Ionomer Cement and Resin-Based Adhesive - Jabbar, Abdul; Aqeel, Maheen; Sahito, Ashique Hussain; Khatri, Muhammad Siddique; Shah, Syed Rizwan; Tariq, Junaid (Pakistan Journal of Health Sciences, 2024)
A high strength of bonding materials is needed for orthodontic attachments to sustain therapeutic forces and patients’ masticatory habits. Objectives: To compare the bond strength of the resin modified glass ionomer cement (RMGIC) and resign based adhesive system which leads to bracket failure in orthodontic treatment (failure to bracket attachment) for the duration of 6 months at the a tertiary care hospital at Hyderabad, Sindh Pakistan. Methods: This comparative cross-sectional study involved 30 patients, each with 20 brackets, using non-probability sampling. Participants were between the ages of 13 and 30 with fully erupted permanent teeth and mild skeletal discrepancies. Quadrants were randomized, and 120 attachments were placed in total, split evenly between the two types of materials. The study involved bonding orthodontic brackets using either composite resin or RMGIC. The teeth were prepared and cleansed, and the brackets were bonded following standard procedures. Patients were monitored each month for six months (six visits) to check for any debonded or missing brackets. Chi-Square test was run to compare bracket failure between two groups. Results: There were significant differences in bracket failure rates between the composite and RMGIC sides. Composite had a lower failure rate, with 90% of brackets remaining intact compared to 63.3% with RMGIC (p=0.04). Gender comparisons showed both male and female participants experienced more failures with RMGIC than with composite, with p-values of 0.039 and 0.038, respectively. Conclusion: RMGIC could not withstand the forces experienced during fixed appliance treatment as effectively as composite resin, resulting in a higher debonding rate.